WOMEN’S ROLE IN THE DEVELOPMENT OF PAJAMBON VILLAGE: INVOLVEMENT, CONTRIBUTIONS, AND CHALLENGES - Safriyana, Safriyana; Sucipto, Chelsea; Kowanda, Joan Bertha; Ekanayake, Kenneth Evan; Nawawi, Robin (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2025)
This study investigates the roles, contributions, and challenges encountered by women in the development of Pajambon Village, located in Kramatmulya District, Kuningan Regency, West Java. Employing a qualitative research methodology, the study explores the equal involvement of both women and men in the community, with no discernible gender disparities in their participation. The findings reveal that women in Pajambon Village make substantial contributions across various domains, including the management of household economies, participation in social activities, and involvement in the village governance structure. Additionally, women prioritize the education of their children and actively engage in workshops aimed at enhancing their skills and knowledge for village development. The local government has established a women’s empowerment group, the Pemberdayaan dan Kesejahteraan Keluarga (PKK), which currently consists of 14 members. This group is further supported and encouraged by the government to engage in entrepreneurial activities that contribute to their economic independence. The study highlights the critical role of women in fostering community development and advancing sustainable rural progress.